Analysis of Process and Formulation Variables on Chitosan based Losartan Potassium Nanoparticles: Preparation, Validation and in vitro Release Kinetics - Singh, Manisha; Kaur, Ramneek; Rajput, Rashi; Agarwal, Shriya; Kumar, Sachin; Sharma, Malvika; Sharma, Aishwarya (Recent Innovations in Chemical Engineering, 2020)
Background: Although many potential therapeutic compounds have been discovered and have exhibited a promising recovery, their effective delivery in the human system has always remained questionable with many pharmacological constraints in delivering them. Amidst all this, the concept of nanomedicine has always assured the potential to overcome the drug delivery complications in the present treatment methods. Losartan Potassium (LP) is indicated in the management of hypertension. Owing to its moderate bioavailability (32%) and a number of side effects due to the oral dosage forms of LP thus, nanoparticles based delivery would be beneficial. Objective: The present study is focused to develop a nanoparticle system of Losartan Potassium, an Angiotensin II receptor antagonist and a well-known promising antihypertensive drug, to conquer its limitation of bioavailability and potential adverse effects. ods: LP Loaded Polymeric Nanoparticles (LP-NPs) were developed by ionic gelation method using Chitosan (CH) and Tripolyphosphate (TPP) for cross linkage in various optimising ratios. After the successful optimisation and synthesis of LP-NPs, the optimised formulation was further characterized by Particle Size Analysis (PSA), Polydispersity Index (PDI), Zeta Potential (ZP), TEM analysis with the in vitro cytotoxicity and permeability evaluation. Results: The results showed the average size of 123.5 ± 1.23nm with polydispersibility score of 0.257 ± 0.079 and charge of -2.74 mV respectively. Further, Transmission Electron Microscopy (TEM) images showed the size range in almost conformity with DLS findings, representing the spherical and smooth morphology. In vitro drug release kinetics estimation showed sustained release routine of the drug and the cell viability studies done on Jurkat cell line displayed lesser cytotoxicity of LP-NPs (99.3 ± 2.28% and 98.17 ± 1.86%) in comparison with the LP only (85.3 ± 2.1% and 71.7 ± 1.07%) at different time periods (12 hours and 24 hours). Conclusion: The aforementioned results confirm the effective fabrication of LP-NPs and indicate that it may further, used on higher model systems to investigate the above parameters and their enhanced effectiveness in hypertension.
Keywords: drug release kinetics